An epidemiological investigation of oral and maxillofacial anomalies in newborns and their relation to parental health in the Ha’il Region, Saudi Arabia - Abdullah F. Alshammari; Najla A. Alhomayan; Rawabi B. Alshmari; Shahad F. Alharbi; Manar A. Alhejaili; Yousef E. Alenezi; Ahmed A. Madfa; Ebtsam A. Aledaili; Freah L. Alshammary; Khlood A. Alkurdi (Scientific Reports)
Abstract This study aimed to determine the prevalence of oral and maxillofacial anomalies among newborns in the Ha’il Region, Saudi Arabia, and to explore associations with parental health, socioeconomic status, and environmental factors. Given the scarcity of regional data on congenital anomalies, this research furthers the understanding of localised health risks and could inform targeted interventions. A cross-sectional hospital-based study was conducted involving 40,000 newborns born between December 2019 and June 2024. Data were collected from medical records and parental interviews at one of the main hospitals in the Ha’il Region. Anomalies were categorised and analysed using the Statistical Package for Social Sciences software, with statistical significance set at p < 0.05. Forty-seven cases (0.146%) of oral and maxillofacial anomalies were identified, with a higher prevalence seen in female newborns. Relationship were found between these anomalies and parental smoking, socioeconomic status, and parental health history. Anomalies, such as cleft lips and palates, were more frequent in females, while other conditions, like the eruption of chlorodontia, were exclusive to males. This study underscores the importance of addressing environmental and socioeconomic factors to prevent congenital anomalies. These findings provide crucial data for healthcare planning in the Ha’il Region, aligning with Saudi’s Vision 2030 objectives related to improving neonatal and maternal care.